ROLE OF MODERN CUSTOMS CLEARANCE TECHNOLOGIES IN IMPLEMENTATION OF INFRASTRUCTURE AND TRANSPORT PROJECTS: REGIONAL ASPECT - Y. Zaletov (Вестник университета)
The article considers and justifies the prospects for utilization of the transport and logistics potential of the Yaroslavl region in terms of the practical application of customs infrastructure facilities of the region to attract additional transportation volumes. The article highlights the role of modern customs clearance technologies in the transport infrastructure optimization.